Bad arguments 100 of the most important fallacies in Western philosophy - Arp. Robert Arp; Barbone, Steven; Bruce, Michael (Wiley Blackwell, 2019)
"Ever decide to avoid a restaurant because of one bad meal? Choose a product because a celebrity endorsed it? Or ignore what a politician says because she's not a member of your party? For as long as people have been discussing, conversing, persuading, advocating, proselytizing, pontificating, or otherwise stating their case, arguments have been vulnerable to false assumptions and faulty reasoning. Drawing upon a long history of logical falsehoods and philosophical flubs, [this book] demonstrates how misguided arguments come to be, what we can do to detect them in the rhetoric of others, and how to avoid using them ourselves"--Back cover.